Dissociation, trauma and the experience of visual hallucinations in post-traumatic stress disorder and schizophrenia - Yann Quidé (BJPsych Open, 2023)
Dissociative behaviours and hallucinations are often reported in trauma-exposed people with schizophrenia spectrum disorders and post-traumatic stress disorder (PTSD). Auditory hallucinations are the most commonly reported type of hallucination, but often co-occur with experiences in other sensory modalities. The phenomenology and the neurobiological systems involved in visual experiences are not well characterised. Are these experiences similar in nature, content or severity among people with schizophrenia and/or PTSD? What are the neurobiological bases of these visual experiences and what is the role of dissociative behaviours in the formation of these experiences? A study by Wearne and colleagues in BJPsych Open aimed to characterise these phenomenological systems in groups of people with PTSD, schizophrenia or both (schizophrenia + PTSD).